Premorbid Hemostasis in Women with a History of Pregnancy Loss - Peshkova, Alina D.; Safiullina, Svetlana I.; Evtugina, Natalia G.; Baras, Yelena S.; Ataullakhanov, Fazoil I.; Weisel, John W.; Litvinov, Rustem I. (Thrombosis and Haemostasis, 2019)
Background Congenital and acquired hemostatic disorders are among the pathogenic factors of pregnancy loss. Studying mechanistic relations between impaired hemostasis and fetal losses is important for the prognosis and prophylaxis of obstetric complications.Objective This article aims to establish latent hemostatic disorders in nonpregnant women as an important premorbid risk factor of pregnancy loss.Methods and Results Hemostasis was characterized using two relatively new in vitro assays, namely thrombodynamics (spatial clot growth) and kinetics of blood clot contraction, which together reflect the hemostatic or thrombotic potential. In addition, platelet functionality was assessed using flow cytometry. Our study included 50 women with a history of pregnancy loss and 30 parous women without previous obstetric complications. In patients with pregnancy loss, hypercoagulability was observed along with significant impairment of blood clot contraction associated with chronic platelet activation and dysfunction. Both hypercoagulability and defective clot contraction were significantly more pronounced in patients with a history of three or more miscarriages compared with patients with a history of one or two miscarriages. In addition, a significant inhibition of clot contraction was found in patients with miscarriage occurring after 10 weeks of gestation compared with those who lost a fetus earlier in pregnancy.Conclusion These results indicate that chronic hypercoagulability and impaired clot contraction constitute a premorbid status in patients with pregnancy loss. The data confirm a significant pathogenic role of hemostatic disorders in pregnancy loss and suggest the predictive value of thrombodynamics and blood clot contraction assays in evaluating the risk of pregnancy loss.
Keywords: blood clotting; contraction of blood clots; recurrent pregnancy loss; miscarriage